IMPLEMENTASI LESSON STUDY FOR LEARNING COMMUNITY (LSLC) PADA LAYANAN BIMBINGAN UNTUK MENINGKATKAN KEPERCAYAAN DIRI - Dahlia Novarianing Asri; Noviyanti Kartika Dewi; Rischa Pramudia Trisnani; Asroful Kadafi (Jurnal Abdimas Bina Bangsa, 2023)
Self-confidence is one of the human aspects that must be owned by every individual, especially students and students to achieve career success, family, education, and so on. However, there are still many students who do not have self-confidence, have not been able to find their strengths and weaknesses. Therefore self-confidence needs to be explored from a young age. High school students are at a developmental stage who are prepared to be immediately ready to work so they need to be instilled with confidence to choose and pursue a job that is in accordance with their field of expertise. To increase students' self-confidence, guidance and counseling services are needed through lesson study for learning community (LSLC) activities which include three stages, namely planning, implementation, and reflection. After being carried out for three cycles, it can be said that through the implementation of Lesson Study for Learning Community (LSLC) in guidance and counseling services, it can increase students' self-confidence. Based on the results of this activity, it will be followed up for lecture activities on campus with the aim of exploring and increasing student confidence